The interaction between androgen receptor and PDGF‐D in the radiation response of prostate carcinoma. Issue 6 (6th January 2016) - Paximadis, Peter; Najy, Abdo J.; Snyder, Michael; Kim, Hyeong‐Reh
Abstract : PURPOSE: To determine the functional relationship between androgen receptor (AR) and PDGF D as it relates to the radiation response of PTEN‐null prostate cancer (PCa) cells and the effect of enzalutamide on these interactions. METHODS AND MATERIALS: Using murine PTEN‐null prostate epithelial cell line and human prostate carcinoma LNCaP (PTEN‐mutant) models, nuclear and cytosolic AR levels were determined by immunoblot analysis and the transcriptional activity of nuclear AR was assessed by RT‐PCR analysis of its target genes with or without irradiation. Cell survival was evaluated by clonogenic assay or sulforhodamine B (SRB) assay upon irradiation in the absence or presence of the AR antagonist enzalutamide. RESULTS: PTEN loss resulted in upregulation of AR expression in a PDGF‐D dependent manner and irradiation selectively increased the nuclear AR protein level and its activity in a murine cell model. When the functional significance of AR in cell survival was tested, treatment with enzalutamide resulted in radiosensitization of human LNCaP cells. Similarly to the murine model, PDGF‐D overexpression increased the nuclear AR level and its transcriptional activity in LNCaP cells. PDGF‐D over‐expression was associated with radioresistance and enzalutamide treatment effectively reversed PDGF‐D‐mediated radioresistance in LNCaP cells. CONCLUSIONS: We have demonstrated that AR, a target of the PTEN and PDGF D‐downstream signaling program, contributes to radiation resistance in human PCa cells. In addition, this study suggests that anti‐androgens such as enzalutamide may serve as radiation sensitizers for the treatment of PCa patients, particularly so in patients with loss of PTEN or overexpression of PDGF‐D. Prostate 76:534–542, 2016 . © 2016 Wiley Periodicals, Inc.